A microscale approach to organic laboratory techniques - Pavia, Donald L.; Lampman, Gary M.; Kriz, George S.; Engel, Randall G. (Cengage Learning, 2018)
"Taking an organic chemistry laboratory course? You need a laboratory textbook you can trust! This proven book gives you what you need to conduct a variety of interesting microscale experiments with safety and ease -- while you develop an understanding of the special techniques these types of experiments require."-- Provided by publisher.
First published in 1976 under title: Introduction to organic laboratory techniques.
Includes indexes.
Keywords: organická chemie; organic chemistry; elektronické knihy; laboratorní cvičení; electronic books; laboratory manuals